Indonesia Transformasi Digital UMKM: Integrasi Manajemen Keuangan dengan Platform Peta Wisata dan Marketplace - Maya Syafriana Effendi; Siti Komsiah; I Gede Agus Suwartane (LPkM Universitas Bakrie, 2026)
This Community Service Program (PKM) was conducted to strengthen the capacity of micro, small, and medium enterprises (MSMEs), homestay owners, and the tourism awareness group (Pokdarwis) in Lebakmuncang Village, Ciwidey, in addressing challenges related to financial management and digital marketing. The primary issues identified include the reliance on manual bookkeeping, limited digital literacy, and the absence of integrated online promotion. The program encompassed several activities, namely awareness sessions on digital transformation, training in simple financial recording, assistance in utilizing tourism map platforms and online marketplaces, as well as digital transaction simulations. A participatory approach was applied through workshops, mentoring, and direct practice. The results indicated a significant improvement in participants’ digital literacy and financial management skills, as evidenced by the increase in the average pretest score of 55 to 82 in the posttest. Furthermore, the program resulted in the establishment of a village tourism website as an integrated promotional platform, the creation of digital business accounts by ten MSMEs, and the online promotion of eight local products. This program has demonstrated a positive impact on enhancing financial management practices, expanding market access, and strengthening product branding. Therefore, integrating financial management digitalization with tourism map and marketplace platforms is proven to be effective in accelerating the digital transformation of MSMEs while supporting the sustainability of the creative economy in tourism villages.